RS2710102 POLYMORPHISM OF THE CNTNAP2 GENE IS RELATED TO AUTISM SUSCEPTIBILITY IN A KAZAKHSTANI POPULATION (International Journal of Biology and Chemistry, 2022)
Autism spectrum disorders (ASDs) represent serious mental development disorders characterized by deficits in verbal and non-verbal communication, reciprocal social interactions and stereotypical behaviors. Genetically determined pathologies of neurodevelopment and synaptic functioning are increasingly considered to be a cause of ASDs. Contactin associated protein-like 2 (CNTNAP2) gene encodes a protein, which plays an essential role in brain development. Genetic variations in the CNTNAP2 gene can perturb its functions, contributing to the genetic predisposition to ASDs. The study aimed to investigate an association of the CNTNAP2 rs2710102 with ASDs in a Kazakhstani population. The study involved patients diagnosed with ASDs and healthy controls of Kazakhstani origin. PCR-RFLP assay was used for the genotyping rs2710102 CNTNAP2 SNP. The distribution of the rs2710102 genotype was under the Hardy-Weinberg equilibrium in both cases and controls. C allele and СС genotype were associated with a significantly increased risk of ASDs (OR = 3.04, 95% CI = 1.96-4.72, p